Pulmonary lesions consistent with disseminated adiaspiromycosis in Egyptian mongooses (Herpestes ichneumon) from Portugal - Matos, A.C. (2016)
Pulmonary lesions consistent with disseminated adiaspiromycosis in Egyptian mongooses (Herpestes ichneumon) from Portugal.